Training Efficiency and Transfer Success in an Extended Real-Time Functional MRI Neurofeedback Training of the Somatomotor Cortex of Healthy Subjects - Auer, Tibor; Schweizer, Renate; Frahm, Jens (Frontiers in Human Neuroscience, 2015)
This study investigated the level of self-regulation of the somato-motor cortices (SMC) attained by an extended functional MRI (fMRI) neurofeedback training. Sixteen healthy subjects performed 12 real-time functional magnetic resonance imaging (rt-fMRI) neurofeedback training sessions within 4 weeks, involving motor imagery of the dominant right as well as the non-dominant left hand. Target regions of interests in the SMC were individually localized prior to the training by overt finger movements. The feedback signal was defined as the difference between fMRI activation in the contra- and ipsilateral SMC and visually presented to the subjects. Training efficiency was determined by an off-line GLM analysis determining the fMRI percent signal changes in the somato-motor cortex (SMC) target areas accomplished during the neurofeedback training. Transfer success was assessed by comparing the pre- and post-training transfer task, i.e. the neurofeedback paradigm without the presentation of the feedback signal. Group results show a distinct increase in feedback performance in the transfer task for the trained group compared to a matched untrained control group, as well as an increase in the time course of the training, indicating an efficient training and a successful transfer. Individual analysis revealed that the training efficiency was not only highly correlated to the transfer success but also predictive. Trainings with at least 12 efficient training runs were associated with a successful transfer outcome. A group analysis of the hemispheric contributions to the feedback performance showed that it is mainly driven by increased fMRI activation in the contralateral SMC, although some individuals relied on ipsilateral deactivation. Training and transfer results showed no difference between left and right hand imagery, with a slight indication of more ipsilateral deactivation in the early right hand trainings.